2012
DOI: 10.31421/ijhs/18/1/995
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cluster thinning, cluster tipping, cluster shredding and defoliation at the flowering on the vegetative and generative vine performance from Kékfrankos Cv.

Abstract: The cluster thinning is a method of the yield regulation.With the removal one part of the clusters, the yield pro leaf area will be lower, hereby the grape and wine quality will be improved. The regulation of the yield can lead to further advantages: the ratio of the vegetative and generative performance of the vines will improve, the condition of the plants will better, the number of the physiological diseases can be reduced and the growth of the shoots and roots can be promoted. The grape growers make the cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 1 publication
(1 reference statement)
0
1
0
1
Order By: Relevance
“…The effectiveness of cluster thinning increased when combined with pinching. The results of our study came on line with that reported by Myriathouses (1966), James et al (1983, Dokoozlian and Hirschfelt (1995), Gamerol et al (2014), Abd-El-Wahab (2006, Prajitna et al (2007), Reynolds et al (2007), Rathea et al (2011), Fazekas et al (2012, Matteo Gatti et al (2012), Nurhan Keskin et al (2013), El-Kenawy ( 2018) Bassiony (2020) and El-Kenawy (2022) Girdling executed by cutting out a thin strip of bark from around the trunk or arms by using a special knife. This practice interrupts the flow of carbohydrates down making more food available for the fruit.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The effectiveness of cluster thinning increased when combined with pinching. The results of our study came on line with that reported by Myriathouses (1966), James et al (1983, Dokoozlian and Hirschfelt (1995), Gamerol et al (2014), Abd-El-Wahab (2006, Prajitna et al (2007), Reynolds et al (2007), Rathea et al (2011), Fazekas et al (2012, Matteo Gatti et al (2012), Nurhan Keskin et al (2013), El-Kenawy ( 2018) Bassiony (2020) and El-Kenawy (2022) Girdling executed by cutting out a thin strip of bark from around the trunk or arms by using a special knife. This practice interrupts the flow of carbohydrates down making more food available for the fruit.…”
Section: Discussionsupporting
confidence: 90%
“…Cluster thinning is a mean to regulate yield that involves removing a portion of the cluster; as a result, the yield per leaf area will be decreased and the quality of the grapes and wine will increase Fazekas et al (2012).…”
Section: Introductionmentioning
confidence: 99%
“…Shoot thinning permits the light to infiltrate the canopy of the vines and increase in the photosynthetic efficiency of the leaves and allows air circulation raising and light intensity inside the canopy as shown in (Table 3), consequently increases of carbohydrate accumulation in of the remained shoots and leaves and translocation of more carbohydrates to berries which, reflects on the enhancement of chemical properties of berries Le Roux, 1992 andGhada, 2015). Also, cluster thinning is a method of the production regulation, with thinning number of cluster or one part of the clusters, the production per leaf area will be lower hereby the quality will be improved in terms of increasing sugars and anthocyanin contents as well as total soluble solids and decreasing total acidity (Fazekas, et al, 2012and Asmaa & Aboryia, 2020. Moreover, the increment in total carbohydrate content of canes as results of removing some shoots lead to enhance in rates of wood ripping, there is a positive relationship between the accumulation of carbohydrates in the cans and the rates of wood ripping (Winkler 1965).…”
Section: Discussionmentioning
confidence: 99%
“…Brezilya'da Sauvignon Blanc üzüm çeşidinde yaprak alma uygulamalarıyla fenolik olgunluğun geliştirildiği belirtilmiş ve özellikle taneler saçma iriliği ile iri koruk aşamasında iken uygulama yapılmasının, üzüm kalitesini belirleyen önemli bir bileşen olduğu ifade edilmiştir (Würz, Allebran, Marcon Filho, de Bem, Brighenti, Rufato, Kretzschmar, 2018). Çiçeklenme zamanında Kekfrankos üzüm çeşidinde yapılan yaprak almanın, suda çözünebilir kuru madde miktarı (SÇKM) ve toplam polifenol içeriğini 4 yıl boyunca değiştirmediği; ancak toplam asitlik (TA), pH ve antosiyanin içeriğini bazı yıllarda değiştirdiği görülmüştür (Fazekas, Göblyös, Bisztray, Gy. Zanathy, 2012).…”
Section: Introductionunclassified